Concentration Pulse Method for the Investigation of Transformation Pathways in a Glycerol-Fed Bioelectrochemical System - Kubannek, Fabian; Moß, Christopher; Huber, Katharina; Overmann, Jörg; Schröder, Uwe; Krewer, Ulrike (Frontiers in Energy Research, 2018)
We investigated transformation pathways and determined rate constants in a continuously operated glycerol-fed bioelectrochemical system under chemostatic conditions by applying concentration pulses of various intermediates. Our methodology does not require the interruption of the continuous operation and is thus in principle suitable for elucidating processes in continuously operated bioreactors in industry as well as in laboratory studies. Specifically for the example of glycerol electrooxidation, pulse responses of current density and effluent concentrations reveal that glycerol is first fermented to acetate, which is then oxidized electrochemically by the anode respiring bacteria. Microbial community analysis confirms this division of labour with a bioanode dominated by Geobacter species 92.8 %) and a much more diverse fermenting community in the planktonic phase, containing mainly Desulfovibrio sp. (45.2 %) and Spiroaetales (18.1 %). Desulfovibrio and Geobacter species are identified as promising candidates for tailored communities for glycerol electro-oxidation. From an acetate concentration pulse experiment, growth rates and half saturation rate constants for the biofilm of K_S = 1.4 mol m^-3 and d(q_max,Ac X_bf)/dt = 933 mmol m^-2 d^-2 are obtained. Furthermore, 1,3-propanediol and glycerol concentration pulse experiments show that the reaction from glycerol to 1,3-propanediol is reversed at high 1,3-propanediol concentrations. The presented methodology allows one to study pathways and extract rate constants through simple experiments in a running system without irreversibly altering the microbial community or destroying the biofilm.